Excessive Left Ventricle Trabeculations versus Cardiomyopathy - Suresh T. Yavagal (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging)
Excessive left ventricle (LV) trabeculations are described at all ages. Current evidence does not support the formation of noncompaction. It is observed in healthy individuals, pregnant women, athletes, and those with cardiac diseases – inherited, acquired, or congenital in origin. Asymptomatic adults with excessive trabeculations (ETs) need no further follow-up. Patients with ET of the LV are managed by symptoms rather than the mere presence or pattern of trabeculations. In infants and children, caution is warranted because of the association of genetic and neuromuscular disorders.